2008
DOI: 10.1542/peds.2008-1315e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternity-Care Practices on Breastfeeding

Abstract: OBJECTIVE. Our goal was to assess the impact of "Baby-Friendly" hospital practices and other maternity-care practices experienced by mothers on breastfeeding duration.METHODS. This analysis of the Infant Feeding Practices Study II focused on mothers who initiated breastfeeding and intended prenatally to breastfeed for Ͼ2 months, with complete data on all variables (n ϭ 1907). Predictor variables included indicators of 6 "Baby-Friendly" practices (breastfeeding initiation within 1 hour of birth, giving only bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
278
5
15

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(324 citation statements)
references
References 13 publications
26
278
5
15
Order By: Relevance
“…[22][23][24][25] There are 2 reasons why our results may differ from previous work. First, our intervention incorporated 3 key structured techniques to reduce any negative impact of formula on breastfeeding: (1) using small, carefully measured volumes of formula, so an infant would not be satiated and demand for breastfeeding would be maintained; (2) using a syringe to prevent the nipple confusion that is associated with a bottle' s nipple; and (3) establishing a clear time frame for terminating formula use.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…[22][23][24][25] There are 2 reasons why our results may differ from previous work. First, our intervention incorporated 3 key structured techniques to reduce any negative impact of formula on breastfeeding: (1) using small, carefully measured volumes of formula, so an infant would not be satiated and demand for breastfeeding would be maintained; (2) using a syringe to prevent the nipple confusion that is associated with a bottle' s nipple; and (3) establishing a clear time frame for terminating formula use.…”
Section: Discussioncontrasting
confidence: 92%
“…First, studies have shown that mothers who feed their infants both by breast and with formula during the birth hospitalization discontinue breastfeeding earlier than mothers who breastfeed exclusively during the birth hospitalization. [22][23][24][25] However, these studies have been observational and might have been confounded by weak prenatal intention to breastfeed. Similarly, mothers who experience problems with initiating breastfeeding, such as poor latch, delayed onset of mature milk production, or nipple pain, might be more likely to use formula and less likely to continue breastfeeding.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] In-hospital provider encouragement is a likely outgrowth of Baby-Friendly requirements for staff education, but has not been studied independently to our knowledge. One study found five specific hospital practices-breastfeeding within the first hour, breast milk only, infant rooming-in, no pacifier use, and receipt of a telephone number for use after discharge-increased breastfeeding duration, but did not mention provider encouragement.…”
Section: Discussionmentioning
confidence: 99%
“…10,[25][26][27][28][29] Extensive early skin-to-skin contact likely increases the duration of any and exclusive breastfeeding. [27][28][29][30][31][32][33][34][35] Delaying procedures such as weighing, measuring, administering eye prophylaxis as well as vitamin K, up to 6 hours after birth, and the initial bath enhances early parent-infant interaction. 10,36 Infants are to be put close to the breast, as soon after birth as is feasible for both mother and infant, to allow for a latch and feeding, ideally within an hour of birth.…”
Section: Prenatalmentioning
confidence: 99%
“…10,36 Infants are to be put close to the breast, as soon after birth as is feasible for both mother and infant, to allow for a latch and feeding, ideally within an hour of birth. 28,[31][32][33][34][35] This practice is to be initiated in the delivery, operating, or recovery room, and every mother should be instructed in proper breastfeeding technique. 5,10,31,[37][38][39][40][41] (I, II-2, II-3, III) 2.…”
Section: Prenatalmentioning
confidence: 99%